Cost Analysis Pasien Chronic Kidney Diseases di Instalasi Rawat Inap RS Soerojo Magelang - Hapsari, Widarika Santi; Kartikawati, Nurfina Dian; Sabaan, Wahid (BORNEO JOURNAL OF PHARMASCIENTECH, 2026)
Chronic Kidney Disease (CKD) is a global health problem with rapidly increasing prevalence and high treatment costs. In developing countries, CKD management is more complex due to the influence of socioeconomic factors and underlying comorbidities. This study aims to obtain an overview of treatment costs and analyze the influence of patient characteristics, comorbidities, and length of stay on direct medical costs for CKD patients at Soerojo Hospital. This study was retrospective using data from CKD patients undergoing inpatient hemodialysis in 2024. Data collected included patient characteristics and direct medical costs. Data analysis was performed descriptively and inferentially using normality tests followed by non-parametric tests (Kruskal-Wallis and Mann-Whitney) to examine cost differences between groups. A total of 87 patients participated in this study. The majority of patients were male (57.74%) and aged ≥60 years (42.53%). Patients with stage 5 CKD dominated (87.36%), most of whom had 1–3 comorbidities (56.32%) with a length of stay ≤5 days (60.92%). The highest direct medical costs were found in patients with stage 5 CKD, especially in the cost of procedures (Rp13,422,222 ± 11,203,121). In general, the cost of procedures was the largest expenditure component. Based on statistical analysis, the variables of the number of comorbidities and length of hospitalization showed a significant relationship (p<.05) with the total cost of care for CKD patients. This study concluded that high clinical complexity due to comorbidities and long LOS were the main predictors of increased direct medical costs.